Effect of Pd-impregnation on performance, sulfur poisoning and tolerance of Ni/GDC anode of solid oxide fuel cells - Zheng, L.; Wang, X.; Zhang, L.; Wang, J.; Jiang, San Ping (Elsevier Ltd, 2012)
Sulfur tolerance of Ni/Gd2O3-CeO2 (Ni/GDC) anodes promoted by impregnated palladium nanoparticles is investigated using the electrochemical impedance spectroscopy (EIS) and galvanostatic polarization techniques in the H2eH2S fuels at 800 C. The anodes are alternately polarized in pure H2 and H2S-containing H2 fuels with H2S concentration gradually increased from 5 to 700 ppm at 200 mA cm2. The degradation in performance for the hydrogen oxidation in H2S-containing H2 fuels especially at low H2S concentration is substantially smaller on Pd-impregnated Ni/GDC cermet anodes, as compared to that on pure Ni/GDC anodes. The potential of Pd-impregnated Ni/GDC electrodes measured in pure H2 decreases by 0.07 V after exposure to H2S-containing H2 fuels, substantially smaller than 0.13 V observed on pure Ni/GDC anodes under identical test conditions. The results show that Pd impregnation significantly enhances the sulfur tolerance of Ni/GDC cermet anodes particularly in the low H2S concentration range (e.g., <100 ppm). The results indicate that the enhanced sulfur tolerance of Pd impregnated Ni/GDC anodes is most likely due to thepromotion effect of impregnated Pd nanoparticles on the hydrogen dissociation and diffusion processes. The reduced moderation of the morphology and microstructure of the anodes in the presence of Pd nanoparticles may be the result of weaker interaction or adsorption of sulfur on Ni and GDC phases.